APPLICATION OF ANTIMONOPOLY LAWS AND ITS INFLUENCE ON BUSINESS COMPETITION IN THE DIGITAL MARKET - Heri Enjang Syahputra; Rolando Marpaung; Roberto Roy Purba; Parlindungan Purba; Iman Sejati Zendrato (Journal of International Islamic Law, Human Right and Public Policy, 2024)
Law Number 5 of 1999 states the definition of monopoly, namely a form of control over the production and/or marketing of goods and/or use of certain services by one actor or one group of business actors. What is meant by business actor is every individual or business entity, whether in the form of a legal entity or non-legal entity which is established and domiciled or carries out activities within the jurisdiction of the Republic of Indonesia, either individually or jointly through an agreement, carrying out various business activities. in the field of economics. The aim of this research is to find out how the law applies to monopolies and its impact on business competition in the digital market. To find out the sanctions applied to business monopolists in the digital market and to find out what are the solutions to prevent business competition in the digital market. The data analysis method used in this research is quantitative analysis. The approach in this research is carried out by examining legal sources from conditions that occur in society that has entered the digital economic era. Research development was carried out in the era of regulations governing business competition that were in effect in Indonesia, and also the policy stakeholders involved in this implementation. Conclusion: The application of anti-monopoly law and its impact on business competition in the digital market is that competition in the business world is an absolute requirement or imperative for the implementation of a market economy. Therefore, the KPPU is aware of the importance of law enforcement in the digital economy era. KPPU is an independent body that cannot be influenced by any party, the Government or other parties who have a conflict of interest, in processing, deciding or investigating a case.